2007
DOI: 10.1002/esp.1569
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of soil erosion rates and controlling factors in the Northern Ethiopian Highlands – towards a sediment budget

Abstract: This paper analyses the factors that control rates and extent of soil erosion processes in the 199 ha May Zegzeg catchment near Hagere Selam in the Tigray Highlands (Northern Ethiopia). This catchment, characterized by high elevations (2100–2650 m a.s.l.) and a subhorizontal structural relief, is typical for the Northern Ethiopian Highlands. Soil loss rates due to various erosion processes, as well as sediment yield rates and rates of sediment deposition within the catchment (essentially induced by recent soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
98
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(102 citation statements)
references
References 47 publications
2
98
1
1
Order By: Relevance
“…It exceeds upland erosion many times, with a soil loss of less than 10 Mg ha −1 a −1 [9]. Contributions of valley bottom gullies to the total soil loss range from 28% in semi-arid Tigray [10] to 90% in the sub-humid highlands in Amhara [5,7]. Valley bottom gullies, therefore, are the main contributors of soil loss in Ethiopian watersheds.…”
Section: Introductionmentioning
confidence: 99%
“…It exceeds upland erosion many times, with a soil loss of less than 10 Mg ha −1 a −1 [9]. Contributions of valley bottom gullies to the total soil loss range from 28% in semi-arid Tigray [10] to 90% in the sub-humid highlands in Amhara [5,7]. Valley bottom gullies, therefore, are the main contributors of soil loss in Ethiopian watersheds.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the factors contributing to high soil erosion rates and land degradation are human induced [15,19]. To meet the increasing demand for food and fuel by the rapidly growing population, the land has been deforested and the subsequent loss of organic matter has led to a lower soil aggregate strength and finer soils.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely reported that presently land degradation rates and erosion rates have been accelerating due to the increasing rural population (Grunder, 1988;Desta et al, 2000;Hurni et al, 2005). At the same time, a large number of soil and water conservation (SWC) practices have been installed attempting to reduce soil loss (Hurni, 1988;Nyssen et al, 2008;Herweg and Ludi, 1999). It is not clear what the effectiveness of these practices is beyond the immediate locations of where they have been tested (Vanmaercke et al, 2010).…”
Section: Introductionmentioning
confidence: 99%